Comparison of the Pharmacokinetics of Generic Versus Branded Obeticholic Acid in a Chinese Population: Effects of Food and Sex. Issue 7 (18th January 2021) - Li, Xiaojiao; Zhang, Hong; Li, Cuiyun; Zheng, Wenbo; Wang, Meng; Wu, Min; Yang, Deming; Hu, Yue; Huo, Dandan; Xu, Zhongnan; Ding, Yanhua; Liu, Li
Abstract: The present study assessed the pharmacokinetics and bioequivalence of a single 10‐mg dose of a generic and the branded formulation (Ocaliva) of obeticholic acid (OCA) in healthy Chinese subjects under fasting and fed conditions. The possible effects of food and sex on the pharmacokinetics of OCA and its 2 active metabolites (glyco‐OCA and tauro‐OCA) were evaluated. Plasma concentrations of OCA and its 2 active metabolites were measured by liquid chromatography‐tandem mass spectrometry. The 90%CIs of the ratios of the test and reference formulations for Cmax, AUC0‐t, and AUC0‐∞ of OCA, glyco‐OCA, and tauro‐OCA were contained entirely within the 80% to 125% range required for bioequivalence under fasting and fed conditions. Plasma exposure of OCA was 30% to 36% higher under fed compared with fasting conditions. Plasma exposure of OCA, glyco‐OCA, and tauro‐OCA was 39% to 66%, 22% to 58%, and 37% to 84% higher, respectively, in women compared with men under fasting and fed conditions. In conclusion, OCA was well tolerated in healthy Chinese subjects under fasting and fed conditions. The single 10‐mg dose of a generic OCA formulation was bioequivalent to Ocaliva. Food and sex impacted the pharmacokinetics of OCA and/or its 2 active metabolites. Further studies are required to determine if these effects are clinically relevant.